PENGEMBANGAN KEBIJAKAN STANDAR BIAYA MASUKAN (SBM): BIAYA KONSUMSI KEGIATAN PENDIDIKAN DAN PELATIHAN - Mahfudin Mahfudin (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2021)
There is no specific regulation in input cost standard regarding the consumption costs of education and training activities causing a high variation in the allocation of unit costs in the consumption. This study aims to determine the need and urgency of special arrangements for education and training consumption costs. The study was conducted using a qualitative descriptive method with data sourced from budget work plans and interviews with several education and training units. The results showed that the unit compiles the allocation costs by referring to one meeting consumption unit as the highest limit. The unit requires special arrangements for training consumption costs. The recommendation from this study is that the regulation of consumption costs for training activities is given at a maximum of 80% of the unit cost of meeting consumption. This arrangement will answer the needs of the unit in making a cost reference, as an efficiency measure and establishing a similarity allocation.